2016
DOI: 10.1177/1934578x1601100423
|View full text |Cite
|
Sign up to set email alerts
|

Search for β-Secretase Inhibitors from Natural Spices

Abstract: The growing number of Alzheimer's disease (AD) patients prompted us to seek effective natural resources for the prevention of AD. We focused on the inhibition of β-secretase, which is known to catalyze the production of senile plaque. Sixteen spices used in Asian countries were selected for the screening. Among the extracts tested, hexane extracts obtained from turmeric, cardamom, long pepper, cinnamon, Sichuan pepper, betel, white turmeric and aromatic ginger showed potent inhibitory activities. Their active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 5 publications
0
21
0
Order By: Relevance
“…In our previous report, hexane and ethyl acetate extracts of Curcuma longa rhizomes showed high potency against β-secretase [1]. The active principles were determined as α-turmerone, βturmerone and ar-turmerone ( Fig.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…In our previous report, hexane and ethyl acetate extracts of Curcuma longa rhizomes showed high potency against β-secretase [1]. The active principles were determined as α-turmerone, βturmerone and ar-turmerone ( Fig.…”
mentioning
confidence: 94%
“…There are only a few studies on the pharmacokinetic properties of turmerones, especially α-and β-turmerone [4] due to the difficulties of isolation and a shortage of the compounds available from natural sources. In fact, the isolation yield was very low in our previous study, possibly due to volatility [1]. Thus, the introduction of an original and efficient isolation method led to the isolation of α-and β-isomers and ar-type turmerones in a pure form that enabled testing to show whether the compounds would pass through the blood-brain barrier to reach the brain in an intact form.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…The screening of various plant materials for the most suitable agents for long-term consumption was performed to obtain naturally originating inhibitors. Among them, turmerones showed relatively high inhibitory activities againt β-secretase at 39, 62 and 92 μM of IC 50 values for α-, β-and ar turmerones, respectively [1]. In addition, turmerones were shown to reach the brain in intact forms when administered orally [2].…”
mentioning
confidence: 98%
“…In a screening study, we found that the sesame seed extract (Sesamum indicum) showed moderate inhibitory activities [2]. Among the tested extracts, ethyl acetate (EtOAc) extract showed the most potent inhibitory activity of 39% at 250 μg/mL.…”
mentioning
confidence: 99%